Vaginose bacteriana e tricomoníase: prevalência, fatores associados e desempenho de testes diagnósticos em mulheres atendidas em ambulatório de ginecologia preventiva - Camargo, Kélvia Cristina de (2022)
INTRODUCTION. Bacterial vaginosis BV and genital infections have a great impact on women's health and are the main causes of demand for health services. GOALS. To investigate the prevalence, associated factors and performance of diagnostic methods for BV and Trichomonas vaginalis TV. METHODS. The thesis is presented in articles, in an original cross-sectional article and a systematic review. The Crosssectional study, conducted with women seen at a preventive gynecology clinic, in the public network of Goiânia, referred to a gynecological consultation. Gynecological examination with evaluation of the characteristics of the vaginal secretion, and the collection of cervicovaginal material for cytological study, fresh examination, vaginal pH, Whiff test, Gram-stained bacterioscopy and the polymerase chain reaction (PCR) for the detection of TV . The samples were analyzed at the Genetic Diversity Laboratory of the Pontifical Catholic University of Goiás (PUC GO) and at the Rômulo Rocha Clinical Analysis Center of the Faculty of Pharmacy of the Federal University of Goiás (FF/UFG). Sociodemographic and behavioral characteristics were analyzed using descriptive statistics. Logistic regression analysis was performed to identify factors associated with BV. The degree of agreement between the clinical characteristics of the vaginal secretion and the different diagnostic methods was evaluated by the Kappa index. The systematic review study was registered in the International Prospective Register of Systematic Reviews (PROSPERO) and performed according to the methodological guidelines of the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses” (PRISMA). The search was performed on PubMed and Scopus databases in September 2021, with no language restriction. Articles were considered eligible if they investigated the prevalence of BV in Brazil; used Amsel's clinical diagnostic criteria or Gram-stained bacterioscopy in women of reproductive age and without comorbidities. Studies were evaluated by two investigators to establish reliability. The risk of bias and the quality of the selected studies were assessed using the Joana Briggs Institute (JBI) tool. RESULTS. The cross-sectional study showed a prevalence of BV, according to the Nugent criteria, of 33.7% and of trichomoniasis by PCR, of 0.5%. The complaint of abnormal vaginal secretion was significantly associated with the diagnosis of BV (OR = 2.2; 95%CI: 1.0- 4.5); The diagnostic accuracy for BV, by the methods of Amsel, Ison & Hay and cytological examination, compared to the Nugent criteria was 35.6%, 97.0% and 84.2%, respectively. The sensitivity and degree of agreement for the diagnosis of TV, by the fresh test was 0.0% and 0.0% and by the cytological test, 100% and 1, respectively. Systematic review included ten articles. The mean prevalence of BV in the included studies was 25.4% (95%CI: 24.0-26.8), ranging from 15.3% (95%CI: 11.8- 19.4) to 51. 0% (95%CI: 43.1-58.7). In three population-based studies, the prevalence ranged from 15.3% (95%CI:11.8-19.4) to 20% (95%CI:16.9-23.6), with a mean of 18,1% (CI:16.0-20.5). In seven clinical-based studies, the prevalence ranged from 18.6% (95%CI: 13.6-25.0) to 51% (95%CI: 43.1-58.7), with an average of 27.2% (95%CI: 24.6-29.9). Factors associated with BV were use of sexual accessories (OR: 2.4; 95%CI: 1.1-4.9), single marital status (OR: 1.4; 95%CI: 1.1-1.8), partner infidelity (OR: 1.5; 95%CI: 1.2-1.9), abnormal vaginal discharge (OR: 1.5; 95%CI:1.2-2.0), presence of trichomoniasis (OR: : 4.1 (95% CI: 1.5-11.5).CONCLUSION. The crosssectional study showed a high prevalence of BV and a low prevalence of TV; The report of abnormal vaginal secretion as the only factor associated with BV; the methods with the best diagnostic performance for BV, compared to the Nugent method, were those Abstract xix of Ison and Hay and cytological examination and cytological examination considered to be easily accessible in the daily clinic. The systematic carried out in this study showed a high prevalence of BV and associated factors linked to sexual behavior, although it is not considered a sexually transmitted infection.